Jasové profily kóm komet jako důsledek procesů disociace a ionizace v atmosférách komet - Zahrádka, Jaromír (Univerzita Pardubice, 1999)
This paper present three bases gaseous models of the comet atmospheres. The models are able elucidate the surface brightness courses of the comet comas. 1. The comet atmosphere which is created by brigftness molecules coming out directly from the nucleus of the comet. 2. The comet atmosphere created by dissociating brightness molecules which arise from the parent molecules which come out from the nucleus of the comet. 3. The comet atmosphere created by brightness molecules which do not dissociate.
Keywords: astronomie; komety; atmosféra; atmosférické procesy; ionizace